PERSEPSI GURU TERHADAP PEMBELAJARAN DALAM JARINGAN (DARING) DAN LUAR JARINGAN (LURING) DI SEKOLAH DASAR SE-KELURAHAN PASAR AMBACANG KECAMATAN KURANJI - Ismira; Darmawan, Ricky (LP2M Universitas Adzkia, 2024)
This research is motivated by problems in the dare and offline learning process. Some of these problems include educators being constrained in paying attention to the learning process, educators being constrained in providing assessments, educators being constrained in seeing developments in students' understanding, educators being unable to utilize learning media during the learning process, students being constrained in answering questions given by educators. . The aim of this research is to determine teachers' perceptions of bold and offline learning, to find out the comparison between teachers' perceptions of bold and offline learning. This type of research is descriptive quantitative research and comparative quantitative research. The results of the research explain that the teacher's perception of dare learning is very good, the Respondent Achievement Level (TCR) for the planning aspect is 89.56%, TCR for the implementation aspect is 88.89%, TCR for the evaluation aspect is 92.71%. Teachers' perceptions of offline learning are very good, TCR for the planning aspect is 90.63%, TCR for the implementation aspect is 94.21%, TCR for the evaluation aspect is 92.68%. There are differences between these two learning systems, seen from the overall average of the answers, namely bold learning got an average of 67.51, while offline learning got an average of 68.16.